Accelerated fatigue measurements using a vibration assembly which loads two specimens simultaneously - Furman, Brandon A.; German, James E.; Wagner, Jeffrey M.; Heninger, Jacob B.; Berke, Ryan B. (American Society of Mechanical Engineers (ASME), 2025)
Fatigue testing is notoriously slow, requiring many hours to obtain 1 data point on an S–N curve. Such tests can be accelerated somewhat using vibration-based techniques, which load on the order of kHz, such that tests which would traditionally have taken multiple days can now be completed in a few hours. This work presents a novel assembly that can further accelerate fatigue testing campaigns by loading multiple specimens simultaneously. The assembly has two resonant modes of interest. The lower frequency mode puts a slightly higher strain on one specimen, and the higher frequency mode puts a slightly higher strain on the other specimen. By alternating between the two modes, fatigue loads are rapidly applied until one specimen fails, during which the unfailed specimen will have experienced the same number of cycles, and therefore has less time remaining until its own failure. The test is paused while the failed specimen is removed and replaced by a fresh specimen. Testing continues in this fashion, alternating between the two resonant modes, until a sufficient number of data points have been maintained to map out an S–N curve. Because the assembly loads two specimens simultaneously, the system is up to twice as efficient compared to testing all specimens individually.
Keywords: 4005 Civil Engineering; 40 Engineering; 4017 Mechanical Engineering; Mechanical Engineering & Transports; 4001 Aerospace engineering; high-cycle fatigue (HCF); vibration-based fatigue testing; digital image correlation (DIC); high-throughput measurements; failure criteria; mechanical properties of materials; stress analysis